Maximizing Non-Profit Engagement on TikTok Through the Effective Application of AIDA in Indonesia - Abidin, Irsyad; Sinduwiatmo, Kukuh (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Social media platforms like TikTok have emerged as powerful marketing tools, enabling organizations to engage with audiences more effectively. Specific Background: Yayasan Lembaga Manajemen Infaq Ukhuwah Islamiyah (LMI Zakat) leverages TikTok to promote its programs, including MSIB (Magang dan Studi Independen Bersertifikat), through its official account @lmizakat. The integration of marketing strategies such as the AIDA (Awareness, Interest, Desire, Action) model provides insight into consumer behavior and the effectiveness of digital content. Knowledge Gap: While studies on social media marketing are extensive, limited research has explored the application of AIDA principles on platforms like TikTok within the context of non-profit organizations. Aims: This research aims to examine the implementation of Integrated Marketing Communication (IMC) by LMI Zakat through TikTok, focusing on how the AIDA model enhances marketing communications and program engagement. Results: Findings indicate that LMI Zakat successfully applied the AIDA model through creative and educational content, which effectively raised brand awareness, generated interest, and increased engagement with the MSIB program. Specifically, the content utilized viral trends to raise awareness and generated desire through informative and persuasive narratives. Novelty: The study provides a unique contribution by highlighting how a zakat organization can use TikTok’s content and viral nature to apply marketing principles, which are typically associated with for-profit sectors. Implications: This research underscores the potential for zakat and non-profit organizations to enhance their marketing strategies through digital platforms like TikTok. Future studies should explore diverse content types and apply AIDA across other social media platforms, contributing to a broader understanding of digital marketing in non-profit contexts. Highlights: TikTok applies AIDA effectively for LMI Zakat's marketing communication. Viral content boosts awareness and engagement with MSIB program. Future studies should explore content variation and cross-platform strategies. Keywords: TikTok marketing, AIDA model, LMI Zakat, non-profit promotion, digital communication